The role and the meaning of unique register small and medium enterprises - M. Tipalina (Вестник университета)
The article analyzes measures of support small and medium enterprises. The author considers unique register of small and medium enterprises and substantiates the necessity of including additional information. Key‘s indicator should be tax regime. The author offers to add the site of the Federal Tax Service of Russia by a new tax calculator of the choice taxation system.